GLOBAL SUPRANATIONAL ACTORS OF INTERNATIONAL RELATIONS AND SOCIAL PHILOSOPHY - I. V. Surma (Vestnik MGIMO-Universiteta)
In article it is shown, that the continued technological and content revolution in the means of mass communication in a number of key indicators complicates the interaction of the participants of international relations, and «information of the press» is of special importance in the modern international relations is the priority, which gives all grounds to attribute the information to the category of factors that determine the fundamental social change in the modern world. Possibilities of modern information society is not always amenable to precise forecast, the action of politicians and international organizations. The Internet space is gradually becoming the main actor in international relations, and one of the most unpleasant aspects of this process is the loss of the information society sustainability. These and other circumstances dictate the need to generate adequate effective state policy of counteraction to cyber terrorism and the development of the new «intellectual technologies» and software tools to control the «dark-web» and analysis of social networks. Social stability of the States will increasingly depend on the correct use of information where it is needed most in this political moment. In article it is shown that the information support of foreign policy and international relations of the stands in one row with such priority issues of world policy as non-proliferation of nuclear weapons, restriction and prohibition of weapons of mass destruction, settlement of regional conflicts and peace-making, strengthening of comprehensive security, the preservation of cultural heritage and promotion of human rights.